Krisis Batas Moral dalam Kebebasan Berekspresi di Media Sosial: Perspektif Hukum Islam terhadap Hak Asasi Manusia di Indonesia: The Moral Boundary Crisis of Freedom of Expression on Social Media: An Islamic Law Perspective on Human Rights in Indonesia - Ayu Rahayu H; Kurniati Kurniati; Musyfikah Ilyas (FAI UIM, 2026)
Freedom of expression on social media has generally been examined from the perspective of human rights or through descriptive applications of maqāshid al-syarī‘ah to digital ethics. However, studies that systematically map hoaxes, hate speech, and privacy violations onto the five dimensions of maqāshid al-syarī‘ah within the context of Indonesia's moral boundary crisis remain limited. This qualitative library research aims to analyse this crisis by establishing an analytical bridge between international human rights standards and maqāshid al-syarī‘ah. The study employs qualitative content analysis of primary Islamic legal sources, international human rights instruments, and relevant academic literature. The findings indicate that freedom of expression is recognised as a right in both the human rights and Islamic legal perspectives, yet each establishes different normative boundaries. Human rights regard restrictions as exceptions to a fundamental right, whereas Islamic law considers moral responsibility an inherent component of that right through maqāshid al-syarī‘ah. Mapping various forms of social media misuse demonstrates that Indonesia's moral boundary crisis is multidimensional and affects nearly all fundamental objectives of Islamic law. This study offers an operational analytical framework that bridges human rights discourse and Islamic legal theory, while highlighting the importance of a maqāshid al-syarī‘ah-based approach to balancing freedom and responsibility in fostering ethical digital interaction.